Structure and physical properties of K0.63RhO2 single crystals - S. H. Yao; B. B. Zhang; J. Zhou; Y. B. Chen; S. T. Zhang; Z. B. Gu; S. T. Dong; Y. F. Chen (AIP Advances, 2012)
K0.63RhO2 single crystals were successfully grown by the flux method. Rietveld refinement of power X-ray diffraction patterns suggests that K0.63RhO2 belongs to the monoclinic P63mmc space group. Transport measurements on K0.63RhO2 revealed metallic behavior. The temperature-dependent resistance is well fitted by a different power law in two different temperature ranges. Antiferromagnetic ordering is observed in the ab-plane of K0.63RhO2 below 50 K. The most attractive feature of K0.63RhO2 is its significant Seebeck coefficient at room temperature (46 μV/cm), which is much greater than that of normal metals. Considered all together, the metallic conductivity, the significant Seebeck effect, and the non-hygroscopic properties of K0.63RhO2 make it a promising candidate material for thermoelectric applications.